2021
DOI: 10.3390/medicina57121331
|View full text |Cite
|
Sign up to set email alerts
|

Early Pacemaker Implantation after Transcatheter Aortic Valve Replacement: Impact of PlasmaBlade™ for Prevention of Device-Associated Bleeding Complications

Abstract: Background and Objectives: Permanent pacemaker implantation (PPI) is frequently required following transcatheter aortic valve replacement (TAVR). Dual antiplatelet therapy (DAPT) or oral anticoagulation therapy (OAK) is often necessary in these patients since they are at higher risk of thromboembolic events due to TAVR implantation, high incidence of coronary artery diseases (CAD) with the necessity of coronary intervention, and high rate of atrial fibrillation with the need of stroke prevention. We sought to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Minimizing trauma by respecting tissue architecture and ensuring good wound closure is extremely important. Electrocautery is widely implemented in most centers, but the use of a plasma electron avalanche knife has been shown to be associated with a reduced incidence of hematoma compared to electrocautery in high-risk patients [74]. Some observational studies advocate for the use of hemostatic agents such as tranexamic acid [75].…”
Section: Hemostasis and Prevention Of Hematomamentioning
confidence: 99%
“…Minimizing trauma by respecting tissue architecture and ensuring good wound closure is extremely important. Electrocautery is widely implemented in most centers, but the use of a plasma electron avalanche knife has been shown to be associated with a reduced incidence of hematoma compared to electrocautery in high-risk patients [74]. Some observational studies advocate for the use of hemostatic agents such as tranexamic acid [75].…”
Section: Hemostasis and Prevention Of Hematomamentioning
confidence: 99%
“…Of 150 procedures performed in the current analysis with the use of low-temperature electrocautery, no clinically significant pocket hematoma developed, although almost 40% of patients were on anticoagulants. A recent study focused on the risk of bleeding in patients on anticoagulants after transcatheter aortic valve implantation demonstrated that the risk of pocket hematoma with low-temperature electrocautery was 1.2% [ 10 ]. As none of the patients from the studied group developed a clinically significant pocket hematoma, and the rates of hematomas from the prior studies with low-temperature electrocautery did not exceed 3.4%, it could be concluded that low-temperature electrocautery allows maintaining low risk of pocket hematoma and lead-related complications [ 4 , 7 ].…”
mentioning
confidence: 99%